Numerical Analysis of Projectile Impact Towards Flax Plate with Different Orientation - PILLAI, PAVIN; Ibrahim, Mohd Norihan (Research Progress in Mechanical and Manufacturing Engineering, 2024)
The study seeks to replicate and assess the effect of gunshots on flax composite plates used in body armor. The study uses ANSYS for velocity impact testing and SOLIDWORKS for model building to assess how various mesh systems and flax plate topologies effect energy dissipation, damage propagation, and plate disintegration. The study aims to better understand the ballistic resistance of flax composites, emphasizing its potential to increase body armor performance. The findings give critical insights into improving composite materials for increased protection, making major contributions to materials science and military equipment developments. This study underlines the practical use of flax composites in the development of lightweight, high-strength protection equipment.